Important roles of the AKR1C2 and SRD5A1 enzymes in progesterone metabolism in endometrial cancer model cell lines. (5th June 2015) - Sinreih, Maša; Anko, Maja; Zukunft, Sven; Adamski, Jerzy; Rižner, Tea Lanišnik
Graphical abstract: Highlights: Progesterone metabolism was studied in the Ishikawa and HEC-1A cell lines. Cell lines differed in the rate of progesterone metabolism. Reductions of 20-ketosteroids were catalyzed mainly by AKR1C2. Silencing of SRD5A1 decreased rate of progesterone metabolism. AKR1C2 and SRD5A1 have crucial roles in progesterone metabolism. Abstract: Endometrial cancer is the most frequently diagnosed gynecological malignancy. It is associated with prolonged exposure to estrogens that is unopposed by progesterone, whereby enhanced metabolism of progesterone may decrease its protective effects, as it can deprive progesterone receptors of their active ligand. Furthermore, the 5α-pregnane metabolites formed can stimulate proliferation and may thus contribute to carcinogenesis. The aims of our study were to: (1) identify and quantify progesterone metabolites formed in the HEC-1A and Ishikawa model cell lines of endometrial cancer; and (2) pinpoint the enzymes involved in progesterone metabolism, and delineate their roles. Progesterone metabolism studies combined with liquid chromatography–tandem mass spectrometry enabled identification and quantification of the metabolites formed in these cells. Further quantitative PCR analysis and small-interfering-RNA-mediated gene silencing identified individual progesterone metabolizing enzymes and their relevant roles. In Ishikawa and HEC-1A cells, progesterone was metabolized mainly to 20α-hydroxy-pregn-4-ene-3-one, 20α-hydroxy-5α-pregnane-3-one, and 5α-pregnane-3α/β, 20α-diol. The major difference between these cell lines was rate of progesterone metabolism, which was faster in HEC-1A cells. In the Ishikawa and HEC-1A cells, expression of AKR1C2 was 110-fold and 6800-fold greater, respectively, than expression of AKR1C1, which suggests that 20-ketosteroid reduction of 5α-pregnanes and 4-pregnenes is catalyzed mainly by AKR1C2. AKR1C1 / AKR1C2 gene silencing showed decreased progesterone metabolism in both cell lines, thus further supporting the significant role of AKR1C2. SRD5A1 was also expressed in these cells, and its silencing confirmed that 5α-reduction is catalyzed by 5α-reductase type 1. Silencing of SRD5A1 also had the most pronounced effects, with decreased rate of progesterone metabolism, and consequently higher concentrations of unmetabolized progesterone. Our data confirm that in model cell lines of endometrial cancer, AKR1C2 and SRD5A1 have crucial roles in progesterone metabolism, and may represent novel targets for treatment.